Determining the Storage of Onions Produced Through Seedlings in Repeated Crop - Mirzasoypovich, Mirzasoliev Mirzaosimjon (International Journal on Integrated Education, 2023)
In the dry, hot climate of the Republic of Uzbekistan, it is scientifically proven that in order to ensure long-term quality preservation of onions grown from seeds and seedlings, it is advisable to plant 35-day-old seedlings on May 21-25 when the seeds are grown in early spring and as a repeated crop.